Psychological and communicative impact on the viewer of social and cultural videos on television - Rushanova Н.Б.; Kalibekuly Д.; Tilepbergen А.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
Currently, media, technology and scientific research allow us to expand and more effectively use communication channels. This, in turn, causes the formation and change of socio-cultural and political concepts in everyday life. This urgent problem required the development of new approaches with an interdisciplinary approach to reconstruct universities and educational institutions. In addition, this problem has led to the emergence of research aimed at studying psychology, sociology, patterns of political behaviour and the influence of the media on the audience. In this context, individuals specializing in the relationship between media and psychology were in demand not only in educational institutions, but also in areas such as politics, architecture, commerce, design and engineering. As a result of the use of media content (both new and traditional), psychology plays an important role. For example, studying the influence of the media, from television to newspapers, from social media channels to billboards, has made it possible to understand new global trends and cultural changes In this context, the main purpose of this research article is to determine theoretical conclusions in the study of psychological aspects in media and communication; to observe the psychological impact of viewers of different ages in media communication; to expand the scope of new approaches and methods in the field of medical psychology. The scientific conclusion of the study involves examining the psychological impact of socio-cultural video presentations on a person through television, identifying the positive or negative impact of socio-cultural manifestations, examining the influence of spiritual and cognitive video presentations and programmes promoting violence, and a comprehensive analysis.